2014
DOI: 10.1186/s12866-014-0204-8
|View full text |Cite
|
Sign up to set email alerts
|

Selenite reduction by the obligate aerobic bacterium Comamonas testosteroni S44 isolated from a metal-contaminated soil

Abstract: BackgroundSelenium (Se) is an essential trace element in most organisms but has to be carefully handled since there is a thin line between beneficial and toxic concentrations. Many bacteria have the ability to reduce selenite (Se(IV)) and (or) selenate (Se(VI)) to red elemental selenium that is less toxic.ResultsA strictly aerobic bacterium, Comamonas testosteroni S44, previously isolated from metal(loid)-contaminated soil in southern China, reduced Se(IV) to red selenium nanoparticles (SeNPs) with sizes rangi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 53 publications
(89 reference statements)
4
55
1
1
Order By: Relevance
“…(Bajaj et al 2012), Zooglea ramigera (Srivastava and Mukhopadhyay 2013), Streptomyces minutiscleroticus M10A62 (Ramya et al 2015), Acinetobacter sp. E6.2 (Durán et al 2015), Comamonas testosteroni S44 (Zheng et al 2014), Klebsiella pneumonia (Fesharaki et al 2010), Lactobacillus sp, Bifidobacter sp., and Streptococcus thermophilus (Eszenyi et al 2011).…”
Section: Selenite Reduction and Biogenesis Of Selenium Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…(Bajaj et al 2012), Zooglea ramigera (Srivastava and Mukhopadhyay 2013), Streptomyces minutiscleroticus M10A62 (Ramya et al 2015), Acinetobacter sp. E6.2 (Durán et al 2015), Comamonas testosteroni S44 (Zheng et al 2014), Klebsiella pneumonia (Fesharaki et al 2010), Lactobacillus sp, Bifidobacter sp., and Streptococcus thermophilus (Eszenyi et al 2011).…”
Section: Selenite Reduction and Biogenesis Of Selenium Nanoparticlesmentioning
confidence: 99%
“…In addition, from the soil of a antimony mine from Lengshuijiang, southern China (Zheng et al 2014), soil of a magnesite mine from Salem, India (Ramya et al 2015), soil of a coal mine from West Bengal, India (Dhanjal and Cameotra 2010), selenium laden agricultural soil of North-East Punjab, India (Bajaj et al 2012), soil of mangrove forest from Bhitarkanika, Orissa, India (Mishra et al 2011), rhizosphere soil of a selenium hyperaccumulator legume grown in seleniferous mine from Sardina, Italy (Lampis et al 2014), rhizosphere of wheat grown in herbicide contaminated soil (Dwivedi et al 2013), and rhizosphere of cereal plants grown in ash-derived volcanic soil of southern Chile (Durán et al 2015). Others include rock fragments of black oil shale from Haenam, Korea (Tam et al 2010), food wastes collected from local market of Giza, Egypt (Khiralla and El-Deeb 2015), sub gingival dental plaque (Pearce et al 2008) etc.…”
Section: Introductionmentioning
confidence: 99%
“…1a), indicating that the microaerobic condition was favorable for growth of strain THL1. Aerobic selenite reduction to elemental selenium by Pseudomonas stutzeri NT-I (Kuroda et al, 2011a), Comamonas testosteroni S44 (Zheng et al, 2014), and Rhizobium selenitireducens (Hunter, 2014) has been reported. Different pathways have been suggested to be involved in microbial selenite reduction, including the Paintertype reaction, the thioredoxin reductase system, siderophoremediated reduction, sulfide-mediated reduction, and dissimilatory reduction (Nancharaiah and Lens, 2015a,b).…”
Section: Selenite Reduction With Organic Carbon As Electron Donor By mentioning
confidence: 98%
“…Different pathways have been suggested to be involved in microbial selenite reduction, including the Paintertype reaction, the thioredoxin reductase system, siderophoremediated reduction, sulfide-mediated reduction, and dissimilatory reduction (Nancharaiah and Lens, 2015a,b). Several enzymes were proposed to be involved in microbiological selenite reduction but no sole gene product was identified (Zheng et al, 2014). Bacterial selenite reduction is believed to occur in the cytoplasm or periplasm, following which the product is transported out of the cell to form elemental selenium nanoparticles (Bajaj et al, 2012;Zheng et al, 2014).…”
Section: Selenite Reduction With Organic Carbon As Electron Donor By mentioning
confidence: 99%
See 1 more Smart Citation